Cognitive abilities and physical activity in community-dwelling elderly - Martins, Emília (2022)
There is evidence of the protective role of the regular practice of physical activity (PA) in relation to the aging cognitive decline. A non-exper- imental quantitative study was developed to explore the relationship between physical activity and cognitive abilities in community-dwelling elderly, ana- lysing the relevance of sociodemographic and health related variables. The convenience sample included 546 participants, aged between 63 and 94 years (72.85+6.55), mostly female (69.6%), from the inland of the country (79.5%) and rural areas (68.2%). For data collection, in addition to the sociodemographic questionnaire, the Montreal Cognitive Assessment (MoCA) and the Modified Baecke Questionnaire were used. Statistical analyses (p<.05) were performed using the SPSS-IBM 27. The results point to a positive and significant relationship between the global scores of MoCA and Baecke (r,- 138, p<.02). Self-perception of health was also positively associated with both the MoCA and Baecke global scores (r,- 23 2» p<.001 and r =.204, p<.Oil) and age showed a negative relationship with those two variables (r,- -.294, p<.001 and r,-- *1 3, p<.001). In the association between MoCA and Baecke, the contrast between genders was quite sharp, with males not show ing any statistical relevance (p>.05) in contrast to females (rs=.182, p<.05). Household (living alone or accompanied) showed significant differences in the MOCA, favourable to those living accompanied (U=-3.96, p>.001). In Baecke, only the gender contrast was statistically significant, favourable to females (U= 25395, pt.05). These data are reinforced by scientific evidence and point to policies that promote the practice of physical activity in elderly.